PENGARUH MOTIVASI BELAJAR DAN KETERAMPILAN KOMUNIKASI INTERPERSONAL TERHADAP HASIL BELAJAR KIMIA MURID DI KELAS XI SMA NEGERI 7 PEKANBARU - Arshi Nur Herdiyanti; Lenny Anwar S; Herdini Herdini (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to analyze the effect of learning motivation (X1) and interpersonal communication skills (X2) partially and simultaneously on students' chemistry learning outcomes (Y). The method used was a quantitative causal-correlational approach with multiple linear regression analysis. The population included all eleventh-grade students at SMA Negeri 7 Pekanbaru, with a random sample of 144 respondents. Data were collected using Likert-scale closed questionnaires for the independent variables and documentation of odd semester final examination scores for the dependent variable. The partial results indicated that learning motivation significantly affected chemistry learning outcomes with a contribution of 25.3% (p < 0.05). Interpersonal communication skills also showed a significant partial effect, contributing 25.5% (p < 0.05). Simultaneous testing demonstrated that both variables had a positive and significant effect on students' chemistry learning outcomes, as evidenced by Fstatistic = 79.126 > Ftable = 3.06 with a significance level of 0.000 < 0.05. The total coefficient of determination (R Square) revealed that the variation in students' chemistry learning outcomes was determined by learning motivation and interpersonal communication by 52.9%, while the remaining 47.1% was influenced by other factors outside this research model. In conclusion, a strong synergy between internal psychological aspects through motivation and social proficiency in interpersonal communication within the classroom is a vital determinant in optimizing students' academic achievement in chemistry.